Student Literacy Skills on Academic Performance as the Implication of Online Learning to University Students - Ulfaika, Romlah; ., Ridwan; Firdausya, Arfa (KnE Social Sciences, 2023)
The students’ literacy skills and some external factors that affect the student’s academic achievements demand a considerable improvement in practice, making it an undeniable context within which to examine the implementation of the literacy strategy in teaching. This study looked into how students’ literacy skills changed after they used an online learning system, as well as what their primary literacy skills were. This study used a survey approach and aimed to collect the data from students about their literacy skills. There are three aspects which are described and found, they are the aspects of explaining scientific phenomena (with the total score of 8.59 points and an average score of competency as 2.86 points, which is in a good category), identifying scientific issues (the total score of each indicator was 9.18 points and the average score of the competency was 3.06, which categorized as a good category) and interpreting and using scientific evidence (the total score was 8.93 points and the average score of the competency was 2.97 which categorized as a good category). It is feasible to conclude that every aspect of the information literacy skill of University of Borneo Tarakan students’ in their academic activities was fairly good. The score in each indicator of competencies were varied, but still, show a stagnant value and serve as evidence for the assessment of students’ information literacy skills. Keywords: literacy skills, academic performance, scientific